M.K. Gandhi, Media, Politics and Society
XVII, 168 p. 4 illus., 1 illus. in color.
Keywords: This Palgrave Pivot showcases new research on M.K. Gandhi and the press, telegraphs and popular culture. Despite Gandhi being the subject of numerous books over the past century, there are few that put journalism centre stage. This edited collection explores both Gandhi’s own approach to the press, but also how different advocacy groups and the media within India and overseas engaged with Gandhi, and his ideology and methodology, to further their own causes. The timeframe of the book extends from the late nineteenth century up to the present, and the case studies draw inspiration from a number of disciplinary approaches.